Teknik Budidaya Tanaman Cabai Merah Pada Musim Hujan di Desa Teluk Piyai Pesisir Kecamatan Kubu Kabupaten Rokan Hilir - Khoiri, M. Amrul; Zafitra, Zafitra; Silvina, Fetmi; Irfandri, Irfandri; Wahyudi, Eko; Irawan, Joni; Ali, Muhammad; Nurhidayah, T. (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
Red chilies are one of the horticultural commodities that have high economic value in Indonesia. Red chili production in Indonesia in 2021 will reach 136 million tons, with Riau province experiencing a decline in production which causes a production deficit in the province. To increase production, it is necessary to improve red chili cultivation techniques. The growth of red chili plants is influenced by internal and external factors, including ideal rainfall ranging from 600 mm/year to 1,250 mm/year. Rainfall that is too high can cause air humidity to increase and plants are more susceptible to disease. Red chili plants also require slightly hot daytime temperatures and sufficient water availability. In the rainy season, the risk of red chili crop failure is high because the plants cannot tolerate standing water. Excess water can cause plant root rot and diseases such as bacterial wilt and anthracnose. Therefore, it is necessary to develop red chili cultivation techniques in the rainy season, such as making the right planting schedule, understanding cultivation techniques, and using technical cultural measures such as making higher beds and using appropriate pesticides. With the right cultivation techniques, it is hoped that it can increase farmers' income and welfare. Red chili cultivation can also provide large profits if revenue is high and production costs are low. Therefore, it is important to optimize efforts to increase red chili production by using appropriate cultivation techniques during the rainy season. The aim of this community service activity is to increase public knowledge about cultivating chili plants during the rainy season in Teluk Piyai Pesisir.